2021
DOI: 10.1007/s00107-020-01638-2
|View full text |Cite
|
Sign up to set email alerts
|

Compression impact behaviour of agglomerated cork at intermediate strain rates

Abstract: This work analyses the influence of intermediate strain rates, between 25 s -1 and 75 s -1 , on compressive behaviour of agglomerated cork. Quasi-static and dynamic compressive tests of an agglomerated cork with two different densities were carried out. This work complements previous research focused on higher strain rates. The influence of strain rate on less studied properties as densification strain or Poisson ratio is also studied. Digital Image Correlation (DIC) is applied in the estimation of the strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…Agglomerated cork can be assimilated to a multiscale foam and the random orientation of the granules intended to obtain an almost isotropic material at the macro level is actually responsible for material anisotropy at the micro level. Through DIC analysis, Gomez et al [ 52 ] disclosed a severe heterogeneity in the specimens responsible for a strong difference in the strain of different points in the sample and similar results were reported by Le Barbenchon et al [ 47 ] and by Sasso et al [ 53 ], who identified several localization bands with different regions experiencing different strains, as reported in Figure 4 .…”
Section: Agglomerated Corksupporting
confidence: 73%
See 4 more Smart Citations
“…Agglomerated cork can be assimilated to a multiscale foam and the random orientation of the granules intended to obtain an almost isotropic material at the macro level is actually responsible for material anisotropy at the micro level. Through DIC analysis, Gomez et al [ 52 ] disclosed a severe heterogeneity in the specimens responsible for a strong difference in the strain of different points in the sample and similar results were reported by Le Barbenchon et al [ 47 ] and by Sasso et al [ 53 ], who identified several localization bands with different regions experiencing different strains, as reported in Figure 4 .…”
Section: Agglomerated Corksupporting
confidence: 73%
“…cork can be assimilated to a multiscale foam and the random orientation of the granules intended to obtain an almost isotropic material at the macro level is actually responsible for material anisotropy at the micro level. Through DIC analysis, Gomez et al [52] disclosed a severe heterogeneity in the specimens responsible for a strong difference in the strain of different points in the sample and similar results were reported by Le Barbenchon et al [47] and by Sasso et al [53], who identified several localization bands with different regions experiencing different strains, as reported in Figure 4. Moving to strain rate sensitivity, many studies investigated the effect of test speed on agglomerated cork exploring the quasi-static regime [47,49,50], i.e., 10 −5 -10 −1 s −1 , the intermediate range [52], i.e., 25-75 s −1 , the low-high range [51,53] i.e., 10 −3 and 100-600 s −1 , and the whole strain rate range [48], i.e., 10 −3 -10 −1 and 60-200 s −1 .…”
Section: Compressive Behaviorsupporting
confidence: 71%
See 3 more Smart Citations